2021
DOI: 10.1155/2021/6655526
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Expression Profiles of Periodontal Ligament Stem Cells from the Periodontitis Microenvironment in Response to Static Mechanical Strain

Abstract: During the period of orthodontic tooth movement, periodontal ligament stem cells (PDLSCs) play an important role in transducing mechanical stimulation and tissue remodeling. However, our previous studies verified that the periodontitis microenvironment causes damage to the biological functions of PDLSCs and abnormal mechanical sensitivity. Long noncoding RNAs (lncRNAs) participate in the inflammatory pathogenesis and development of many diseases. Whether lncRNAs are abnormally expressed in PDLSCs obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In total, 13 of the 50 studies broadly explored the expression profiling of PDL cells using microarray or RNA sequencing (RNA-seq) ( Table 1 ). These studies investigated the lncRNA expression profiles of PDL cells subjected to osteogenic induction [ 28 , 29 , 30 , 35 , 36 ] and mechanical stress [ 37 , 38 , 39 , 40 , 41 ]; some compared PDL cells’ expression profiles with those of other cell types, including bone marrow stem cells (BMSCs) [ 27 ], gingival mesenchymal stem cells (GMSCs) [ 42 ], and dental follicle cells (DFCs) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 13 of the 50 studies broadly explored the expression profiling of PDL cells using microarray or RNA sequencing (RNA-seq) ( Table 1 ). These studies investigated the lncRNA expression profiles of PDL cells subjected to osteogenic induction [ 28 , 29 , 30 , 35 , 36 ] and mechanical stress [ 37 , 38 , 39 , 40 , 41 ]; some compared PDL cells’ expression profiles with those of other cell types, including bone marrow stem cells (BMSCs) [ 27 ], gingival mesenchymal stem cells (GMSCs) [ 42 ], and dental follicle cells (DFCs) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the 13 studies that explored lncRNA expression profiles in PDL cells, 6 used microarray analysis and 7 used RNA-seq methods [ 27 , 28 , 29 , 30 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Recent developments in RNA-seq techniques offer enormous potential for transcriptome characterization as they are reliable tools for elucidating genetic and metabolic pathways involved in biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long noncoding RNAs (lncRNAs), consisting of 200 or more nucleotides, regulate many biological and pathological processes and play roles in periodontitis [ 13 ]. Studies have reported amounts of lncRNAs that are differentially expressed between hPDLSCs and pPDLSCs exposed to SMS [ 14 ], and some of these lncRNAs affect the osteogenic differentiation capacity of PDLSCs [ 15 , 16 ]. For example, lncRNA-XIST promotes the osteogenesis of PDLSCs and is expressed at lower levels in strain-exposed pPDLSCs than in strain-exposed hPDLSCs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%